2018
DOI: 10.5093/jwop2018a16
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Team Effectiveness: The Mediating Role of Affective Team Commitment

Abstract: In the present day, organizations worldwide tend to structure their work around teams and workgroups 1 to perform more rapidly, flexibly, and adaptively (Kozlowski & Ilgen, 2006). The various applications of teams in organizations have led to an approach that emphasizes their nature as finalized systems and the emergence of a new focus dedicated to this issue: effectiveness (Mathieu, Maynard, Rapp, & Gilson, 2008). Because the effectiveness of teams matters for individual, organizational, and societal well-bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
0
14
0
4
Order By: Relevance
“…Previous research revealed that the ability of the leader to express emotions, values and motives in a transparent and authentic way contributes positively to team commitment (Mazutis and Slawinski, 2008;Darvish and Rezaei, 2011;Paolucci et al, 2018), clearly highlighting the importance of emotional transparency for commitment. In the emotions as social information (EASI) model, van Kleef (2016) identifies affective reactions as one of the two mechanisms that explains the effects of emotional expression on behaviors (the other is inferential processes).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research revealed that the ability of the leader to express emotions, values and motives in a transparent and authentic way contributes positively to team commitment (Mazutis and Slawinski, 2008;Darvish and Rezaei, 2011;Paolucci et al, 2018), clearly highlighting the importance of emotional transparency for commitment. In the emotions as social information (EASI) model, van Kleef (2016) identifies affective reactions as one of the two mechanisms that explains the effects of emotional expression on behaviors (the other is inferential processes).…”
Section: Introductionmentioning
confidence: 99%
“…Support of a leader refers to the characteristics of a leader which make them a guide, motivator and incentive for a team. The existence of leader support can help a team to achieve their common goals in a more effective way (Paolucci, Dimas, Zappalà, Lourenço, Rebelo, 2018). The next aspect is trust which is defined as interpersonal cooperation and it is formed by way of face-to-face interaction, empathy, respect and honesty (Hakanen, Häkkinen, Soudunsaari, 2015).…”
Section: Wstępmentioning
confidence: 99%
“…Wsparcie lidera to jego cechy, które czynią go przewodnikiem, motywatorem i bodźcem dla zespołu. Istnienie wsparcia lidera może pomóc zespołowi w osiągnięciu wspólnych celów w bardziej efektywny sposób (Paolucci, Dimas, Zappalà, Lourenço, Rebelo, 2018). Kolejnym aspektem jest zaufanie, które definiuje się jako współpracę międzyludzką i kształtuje się na drodze bezpośredniej interakcji, empatii, szacunku i uczciwości (Hakanen, Häkkinen, Soudunsaari, 2015).…”
Section: Wstępunclassified
“…desempenho, viabilidade), e que esta relação é mediada por processos de equipa como os comportamentos de suporte (Pessoa et al, 2018) e aprendizagem (e.g. Rebelo et al, 2018), bem como por estados emergentes como a implicação afetiva (Paolucci et al,, 2018). Mais, Dimas et al (2018) realizaram um estudo com 90 equipas organizacionais em que verificaram que a liderança transformacional promove a resiliência da equipa, o que por sua vez está positivamente relacionado com a viabilidade da equipa e a qualidade da experiência de trabalho da equipa.…”
Section: A Eficácia Do Trabalho Em Equipaunclassified